PELATIHAN GAMOLAN DAN TARI SIGEH PENGUTEN BAGI PELAJAR SEBAGAI USAHA PENGEMBANGAN SEBUAH KAWASAN WISATA BUDAYA DI DESA NEGERI KATON KABUPATEN PESAWARAN - Hasyim Kan; Nabila Kurnia Adzan; Erizal Barnawi (Jurusan Pendidikan Bahasa dan Sastra Indonesia, FKIP Universitas Lampung, 2022)
The objective of the community service program for the Negeri Katon village is to make the community have skills to play gamolan to improve community knowledge and economy. Gamolan so far has only been taught as an art subject in schools and higher education. This community service program can be an important part, of the specific character, and reflection of the community. The community is expected to be able to play gamolan individually or in groups to play along with dances. The gamolan and sigeh penguten training are a combination between gamolan playing and dancing learning. Varying lectures are delivered by educators to explain the benefits of playing gamolan, the gamolan parts and methods to play it, and practicing gamolan to play along with sigeh penguten dancing. The training members are muli (girls) and meranai (boys) of junior and senior high school ages in Negeri Katon village of Pesawaran regency. The result shows that girls and boys in junior and senior high schools in Negeri Katon village did not know how to play gamolan and the dance. After training, they understand, internalize, and preserve the gamolan and the dance, and they would develop and promote them through social media so other people would know better about Negeri Katon village as an attractive and interesting cultural village to attract them coming to see the Negeri Katon village as a cultural tourism object.